2013
DOI: 10.1371/journal.pone.0070741
|View full text |Cite
|
Sign up to set email alerts
|

Early Cambrian Pentamerous Cubozoan Embryos from South China

Abstract: BackgroundExtant cubozoans are voracious predators characterized by their square shape, four evenly spaced outstretched tentacles and well-developed eyes. A few cubozoan fossils are known from the Middle Cambrian Marjum Formation of Utah and the well-known Carboniferous Mazon Creek Formation of Illinois. Undisputed cubozoan fossils were previously unknown from the early Cambrian; by that time probably all representatives of the living marine phyla, especially those of basal animals, should have evolved.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(110 citation statements)
references
References 37 publications
(57 reference statements)
3
107
0
Order By: Relevance
“…Han et al . () did not share the concerns of Steiner et al . () in fitting a cnidarian bodyplan to the internal structures described by Dong et al .…”
Section: History Of Research Into Olivooidesmentioning
confidence: 71%
“…Han et al . () did not share the concerns of Steiner et al . () in fitting a cnidarian bodyplan to the internal structures described by Dong et al .…”
Section: History Of Research Into Olivooidesmentioning
confidence: 71%
“…A small number of specimens have shown that the external pentaradial symmetry is imposed more fundamentally upon the internal anatomy which has been preserved in only the most exceptional of circumstances, revealing a series of circumference parallel walls with pentaradial divisions and diverticulations, leading to an open adapertural space otherwise occupied by an axial pentaradial process (Dong et al 2013 ;Han et al 2013 ). Additionally, a set of two juxtaposed pentaradial objects has been described in association with Olivooides and interpreted as ephyrae (juvenile medusae) in the process of strobilation (budding in scyphozoan cnidarians; see Chapter 6 ) (Dong et al 2013 ).…”
Section: Olivooides and Quadrapyrgitesmentioning
confidence: 99%
“…Debate over the affi nity of the olivooids has been wide-ranging, including echinoderms , scalidophorans (Steiner et al 2014 ), cnidarians (Bengtson and Yue 1997 ;Yue and Bengtson 1999 ;Han et al 2013 ), and diploblastic stem-eumetazoans (Yasui et al 2013 ). The hypothesis of echinoderm affi nity is based on little more than pentaradial symmetry and can be rejected since the olivooids lack key echinoderm apomorphies, not least a mineralised skeleton comprised of calcite stereom (Dong et al 2013 ;Han et al 2013 ;Steiner et al 2014 ).…”
Section: Olivooides and Quadrapyrgitesmentioning
confidence: 99%
See 2 more Smart Citations